Genetic Relationships of Cultivated Avocado Germplasm in Gorontalo Based on Qualitative Traits - Magfirahtul Jannah; Febriyanti Febriyanti; Ilyas H. Husain; Nur Fadhillah Pembengo; Tiska Igirisa (Jurnal Penelitian Pendidikan IPA, 2025)
The avocado (Persea americana), a recognized superfood and valuable horticultural commodity, exhibits significant morphological diversity due to long-term adaptation to various habitats, enhancing biodiversity. This study analyzed the diversity and genetic relationships of cultivated avocados in Gorontalo Regency. Using the Descriptors for Avocado (Persea spp.), 25 qualitative morphological traits were characterized, and a phenetic analysis of 17 accessions was conducted using UPGMA with Jaccard’s Coefficient. Accessions were collected from six villages across four sub-districts: Dulamayo Barat, Dumati, Hepuhulawa, Kayubulan, Kayumerah, and Tridarma. Results revealed substantial diversity in traits such as tree shape, and the morphology of stems, leaves, fruits, and seeds. Phenetic analysis grouped the accessions into two clades: Clade A, comprising 15 accessions in two clusters (similarity index: 64.7-29.0%), and Clade B, containing two accessions in one cluster (similarity index: 64.7%). Clades A and B exhibited a distant relationship, with a similarity index of 23.6%. Conserving the diverse avocado germplasm is essential for safeguarding genetic resources and supporting breeding programs to develop superior varieties in Gorontalo